PENINGKATAN KEMAMPUAN MENULIS DIALOG SEDERHANA SESUAI UNGGAH-UNGGUH BAHASA JAWA DENGAN MENGGUNAKAN METODE ROLE PLAYING - Rinaldi, Ifan Mustika (Universitas Negeri Surabaya, 2020)
ABSTRACTThis study aimed to describe the ability to write a simple Polite Javenese dialogue using Role Playing of which the materials to write simple Javanese dialogue can be easily learnt and fun. This research was conducted in fourth graders of Growong Elementary School, sub district of Tempuran, Magelang district. Design of this research was Classroom Action Research using two circles. Each circles consisted of three steps such as (1) planning, (2) action and observation, (3) reflection. Data were collected using observation and test. Observation was used to observe teacher?s and students? activities in teaching and learning process while, test was to measure students? writing ability to make simple polite Javanese dialogue. Data were analyzed with quantitative descriptive. The results of the first cycle study were (1) the feasibility of Role Playing the method for teacher's activity was 95% and its completeness was 87.5% (very good), (2) the percentage of students? activity was 66.46%, (3) teachers? respond was positive in implementing Role Playing method, (4) the percentage of students? response to the implementation of Role Playing method was 85.71% (12 students), (5) the average score of students? ability to make simple polite Javanese dialogue was 72.21 and the classroom completeness was 64.29%. The data shows that the indicators of success in the aspect of teacher? activities, students? activities and tests for ability to write simple dialogue was not reached so that the study continued into the second cycle with some improvements. The results of the second cycle study were (1) the feasibility of Role Playing the method for teacher's activity was 100% and its completeness was 97.5% (very good); (2) the percentage of students? activity was 81.41%, (3) teachers? respond was positive in implementing Role Playing method, (4) the percentage of students? response to the implementation of Role Playing method was 100% (14 students), (5) the average score of students? ability to make simple polite Javanese dialogue was 86.79 and the classroom completeness was 100%. Based on these data, all indicators of success has been achieved so that the study was stopped in the second cycle. Therefore, it can be concluded that the implementation of Role Playing method can improve the ability to write simple polite Javanese dialogue for 4th graders of Growong Elementary School.Keywords: Ability to write simple dialogue, Role Playing, unggah-ungguh bahasa Jawa (polite Javanese).ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kemampuan menulis dialog sederhana sesuai unggah-ungguh bahasa Jawa dengan menggunakan metode Role Playing. Melalui metode Role Playing, materi menulis dialog sederhana sesuai unggah-ungguh bahasa Jawa dapat dipelajari dengan lebih mudah dan menyenangkan. Penelitian ini dilakukan pada siswa kelas IV. Desain penelitian ini adalah Penelitian Tindakan Kelas. Penelitian dilakukan dalam dua siklus. Setiap siklus terdiri dari tahap (1) perencanaan, (2) tindakan dan obervasi, (3) refleksi. Data didapatkan melalui observasi dan tes. Observasi digunakan untuk mengamati kegiatan yang dilakukan guru dan siswa selama proses pembelajaran. Sedangkan tes dilakukan untuk mengukur kemampuan menulis dialog sederhana siswa. Analisis data yang digunakan adalah deskriptif kuantitaif. Hasil penelitian siklus I adalah (1) keterlaksanaan metode Role Playing ditinjau dari aktivitas guru sebesar 95% dan ketercapaiannya sebesar 87,5% (sangat baik), (2) persentase aktivitas siswa sebesar 66,46%, (3) guru merespons positif terhadap penerapan metode Role Playing, (4) persentase respons siswa terhadap penerapan metode Role Playing sebesar 85,71% (12 siswa), (5) nilai rata-rata kemampuan menulis dialog sederhana sesuai unggah-ungguh bahasa Jawa siswa sebesar 72,21 dan ketuntasan klasikal sebesar 64,29%. Data tersebut menunjukkan bahwa indikator keberhasilan pada aspek aktivitas guru, aktivitas siswa dan tes kemampuan menulis dialog sederhana belum tercapai sehingga penelitian dilanjutkan ke siklus II dengan beberapa perbaikan. Hasil penelitian siklus II adalah (1) keterlaksanaan metode Role Playing ditinjau dari aktivitas guru sebesar 100% dan ketercapaiannya sebesar 97,5% (sangat baik); (2) persentase aktivitas siswa sebesar 81,41%, (3) guru merespons positif terhadap penerapan metode Role Playing, (4) persentase respons siswa terhadap penerapan metode Role Playing sebesar 100% (14 siswa), (5) nilai rata-rata kemampuan menulis dialog sederhana sesuai unggah-ungguh bahasa Jawa siswa sebesar 86,79 dan ketuntasan klasikal sebesar 100%. Berdasarkan data tersebut berarti semua indikator keberhasilan sudah tercapai sehingga penelitian dihentikan di siklus II. Hal ini berarti penerapan metode Role Playing dapat meningkatkan kemampuan dalam menulis dialog sederhana sesuai unggah-ungguh bahasa Jawa siswa kelas IV Sekolah Dasar Negeri Growong. Kata Kunci: Kemampuan Menulis Dialog Sederhana, Role Playing, Unggah-Ungguh Bahasa Jawa, Role Playing.